Deskripsi Kemampuan Literasi Sains Aspek Kompetensi Peserta Didik Kelas VIII SMP Negeri 21 Makassar - Metha Amelia; Muh. Tawil; Arie Arma Arsyad (Universitas Negeri Makassar, 2024)
This study aims to determine how high the level of scientific literacy ability in the competency aspect of class VIII students at SMPN 21 Makassar. This research is a descriptive survey research using a quantitative approach. The population in this study were students of class VIII SMPN 21 Makassar as many as 207 students spread over 8 classes. Sampling used the Random Sampling technique and determined the number of samples using the slovin formula, namely 136 students. The research instrument was in the form of 20 multiple choice questions. Based on the results of data analysis it is known that the scientific literacy ability level in the competency aspect of class VIII students at SMPN 21 Makassar is 54.66% which is included in the low category.